Saving behavior among IPTA students in Kota Bharu / Aini Raihan Mansor, Nurhafizah Hamdan and Khadijah Said - Mansor, Aini Raihan; Hamdan, Nurhafizah; Said, Khadijah (2017)
This research project identifies the saving behavior among IPTA students in Kota Bharu involving the demographic characteristics of respondent and individual perception towards saving behavior. Saving plays an important role in the process of economic growth and development. Saving can be defined as the part of an individual’s income that is not spent. This study aims to determine the significant difference of demographic profile (gender, course and family income) towards saving behavior and to determine the relationship between financial literacy, parental socialization, peer influence, self-control and saving behavior. Besides that, this study also aim to determine the significant effect of financial literacy, parental socialization, peer influence, self-control on saving behavior. A total of 302 respondents were randomly selected using Multi Stage Cluster Sampling. This study collected the data through distributed questionnaires to all selected respondent. The data were analyzed using SPSS 19.0 and Structural Equation Modeling (SEM) technique with the use of Partial Least Square approach (PLS). The overall findings of this study showed that gender and family income are influence the saving behavior. While the determinants that contributed the saving behavior was financial literacy, parental socialization and self-control. The several suggestions are everyone must put the goal of saving money and need to achieve to make it easier in the future and saving behavior is very important and should be practiced in everyday life